Fetal alcohol syndrome: Diagnosis and management - Sahoo, Tanushree; Gulla, Krishna Mohan (Indian Journal of Child Health, 2019)
With the increase in urbanization and socioeconomic status in Indian subcontinent, the incidence of alcoholism in women is rising alarmingly, so as its consumption in pregnancy. Alcoholism in pregnancy is associated with a wide spectrum of neurological manifestations covered under the umbrella of fetal alcohol syndrome (FAS). Hence, it is the need of the hour that the physicians should be aware of the condition and its phenotypic variations. In the absence of the availability of any definite treatment, supportive treatment and abstinence during pregnancy are the only available solution for preventing further progress and recurrence in future pregnancy.